Influence of different types of polypropylene fibre on the mechanical properties of high-strength oil palm shell lightweight concrete - Yew, M.K.; Mahmud, H.B.; Ang, B.C.; Yew, M.C. (Elsevier, 2015)
This study aims to investigate the use of various polypropylene (PP) fibres with different aspect ratio and geometry to enhance the mechanical properties of oil palm shell fibre-reinforced lightweight concrete. The volume fractions (Vf) of 0.25%, 0.375% and 0.5% were studied for each fibre. As various PP fibres were added into oil palm shell fibre reinforced concrete, the marginal density reduction was reported. The effectiveness of new types of PP fibres to increase the compressive strength at later ages was more pronounced than at early age. It is found that low volume fractions of polypropylene twisted bundle (PPTB) fibres are more effective in improving the flexural strength of OPS concrete compared to its splitting tensile strength. The average modulus of elasticity (E value) is obtained to be 13.4 GPa for all mixes, which is higher than the values reported in previous studies. An increase in the percentage third load compressive strength of 0.5% PPTB fibre of up to 11% was reported. Hence, this new types of PP fibres is a promising alternative solution to compensate lower mechanical properties for lightweight concrete.